已知列表 x = [1, 3,
2],那么执行语句 a, b, c =
map(str,sorted(x)) 之后, c 的值为 ( )
A: '3'
B: 3
C: 2
D: 1
2],那么执行语句 a, b, c =
map(str,sorted(x)) 之后, c 的值为 ( )
A: '3'
B: 3
C: 2
D: 1
举一反三
- 已知列表 x = [1, 3, 2],那么执行语句 a, b, c = map(str,sorted(x)) 之后,c的值为______。 A: 3 B: '3' C: 1 D: '1'
- 已知列表 x = [1, 3, 2],那么执行语句 a, b, c = map(str,<br/>sorted______ ) 之后,c的值为 <br/>(______ (______ ) )。
- 已知列表 x = [1, 3, 2],那么执行语句 a, b, c = sorted(x) 之后,b 的值为 ( ) A: 2 B: 1 C: 3 D: 0
- 已知列表 x = [1, 3, 2],那么执行语句 a, b, c = sorted(x) 之后,b的值为____。
- 已知列表 x = ['1', '2'],那么执行语句 x.append(['3']) 之后,x 的值为 ( ) A: ['1', '2', '3'] B: ['1', ''2, ['3']] C: ['1'] D: ['3']